Pendidikan Moral Sebagai Wadah Pembentuk Calon Pendidik Yang Berkarakter - Kadek Ari Wisudayanti (Edukasi: Jurnal Pendidikan Dasar, 2022)
Moral education is a learning that aims to form a person who understands morals, the main focus is the smart young generation from elementary to university level. The character or personality of a teacher not only determines his authority in front of students, but also in front of the community. The personality characteristics of a good teacher are very important for smart teachers so that they can control and control the behavior of their students through habituation patterns. It is a big mistake if a teacher only teaches memorization and memory material to students without paying attention to aspects of attitudes and social skills. Habituation of good attitudes and provision of social skills are very important to build student character.